2007
DOI: 10.1099/mic.0.2006/002543-0
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of water/gas oil emulsions by desulfurizing cells of Gordonia alkanivorans RIPI90A

Abstract: It has been previously reported that resting-cells, non-proliferating cells, of Gordonia alkanivorans RIPI90A can convert dibenzothiophene (DBT) to 2-hydroxybiphenyl (2-HBP) via the 4S pathway in a biphasic system. The main goal of the current work was to study the behaviour of resting-cells of this strain in biphasic organic media. Resting-cells showed strong affinity for sulfurous organic substrates and were able to stabilize water/gas oil emulsions by attaching to the interface without decreasing the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 31 publications
1
35
1
Order By: Relevance
“…The production of DBT desulfurizing enzymes has been shown to be inhibited by inorganic sulfate (Alves et al, 2005;Gunam et al, 2006;Lee et al, 1995;Li et al, 1996;Mohebali et al, 2007a;Noda et al, 2002;Ohshiro et al, 1996b;Rhee et al, 1998;Wang & Krawiec, 1996). No radiolabelled sulfite was produced in incubations of sulfate-grown R. erythropolis IGTS8 resting cells with […”
Section: Regulation and Repression Of Dsz Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of DBT desulfurizing enzymes has been shown to be inhibited by inorganic sulfate (Alves et al, 2005;Gunam et al, 2006;Lee et al, 1995;Li et al, 1996;Mohebali et al, 2007a;Noda et al, 2002;Ohshiro et al, 1996b;Rhee et al, 1998;Wang & Krawiec, 1996). No radiolabelled sulfite was produced in incubations of sulfate-grown R. erythropolis IGTS8 resting cells with […”
Section: Regulation and Repression Of Dsz Genesmentioning
confidence: 99%
“…The hydrophobic nature of several desulfurizing bacteria, e.g. R. erythropolis IGTS8 (Monticello, 2000) and Gordonia alkanivorans RIPI90A (Mohebali et al, 2007b), makes the resting cells adhere preferentially to the oil-water interface in oil-water systems. This property is advantageous, as the sulfur compounds are directly transferred from the oil into the cells, decreasing process mass transfer limitations.…”
Section: Phase Contact and Separationmentioning
confidence: 99%
“…The mixture was mixed vigorously for 2 min and allowed to stand for 24 h at room temperature. The emulsification index (E 24 ) was calculated by dividing the measured height of the emulsion layer by the total height of the mixture and multiplying it by 100 [29,32,33].…”
Section: Determination Of Emulsification Activitymentioning
confidence: 99%
“…The reduction of sulfur in the spent engine oil is necessary to obtain ultra low sulfur diesel through pyrolysis. Biodesulfurization of spent oil using suitable microorganisms may serve as a promising process to eliminate the organosulfur compounds, as already studied in case of hydrodesulfurized diesel obtained from petroleum crude (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In case of diesel, dibenzothiophene (DBT) and its alkylated homologues are biodesulfurized by the action of microorganisms like Rhodococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…These biosurfactants are value-added products which can be used for different industrial purposes, mainly as drilling mud in advanced oil recovery from wells (25). Although a few research studies on the biodesulfurization of diesel have already been reported (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Only a few (26) have been reported on the biodesulfurization of spent engine oil are available in the literature.…”
Section: Introductionmentioning
confidence: 99%